An Analysis Of Teacher Made Test of Discrimination Power of SMAK Giovanni Kupang - chamelya vivi crystanty sene (STKIP PGRI Lubuklinggau, 2021)
This research takes a look at item evaluation constructed through English teachers of SMAK Giovanni Kupang. Specifically it focuses on the problem of Discrimination Power of test items. It aimed to know the quality of discrimination Power of the test items. Design used in this research was mix method. Data resource was semester test item of grade X. The instrument used was documents containing 40 multiple choice test items constructed by the English teacher in SMAK Giovanni Kupang, The result of this study showed that only 87.5% of discrimination Power.